Upaya Peningkatan Kesehatan Lansia Sehat Mandiri dan Produktif di Kelurahan Legok - Suri, Marta; Yanti, Rahmi Dwi; Putri, Vevi Suryenti (3031-8572, 2024)
Old age is a natural process experienced by everyone that cannot be avoided. Naturally, the process of getting old results in a decline in physical and mental abilities. In general, more organ disorders are complained of by the elderly. The aging process in individuals certainly has an impact on various aspects of life, especially health, because as age increases, the function of organs in the body will decrease due to natural factors or due to disease. Thus, the main focus or approach to health services or efforts for the elderly needs to accommodate and be linked to the degenerative processes experienced by the elderly population. The implementation of this Community Service was carried out on January 20, 2024. The implementation of the Counseling was carried out by gathering the elderly in the Legok Village, Jambi City with 10 elderly counseling participants. During the counseling activity on the health of healthy, independent and productive elderly in the Legok Village, Jambi City, it went smoothly and the counseling participants were very active and there were several participants who asked questions. Counseling on healthy, independent and productive elderly was carried out face-to-face directly by conducting counseling using leaflet media